Le protesi di gomito: considerazioni cliniche e metodologiche - Moscolo, A.; Micheloni, G.; Mazzi, M.; Giaretta, S. (Lo Scalpello - Journal, 2019)
ELBOW ARTHROPLASTY: CLINICAL AND METHODOLOGIES CONSIDERATIONSElbow replacement has been typically used for patients suffering from autoimmune arthritis resistant to medicaltherapy; at present, some of its main indications are chronic degenerative diseases, like primary osteoarthritis, andfurther distal humerus fractures, not otherwise synthesized, in selected cases. They are classified as total arthroplastyor partial arthroplasty (the latter recommended in younger patients in the absence of joint instability); and asconstrained or unconstrained prostheses (more frequently implanted and characterised by kinematic patterns moresimilar to normal); regardless of the indication, a 5-year survival rate between 72 and 84% is reported.It is essential to verify the joint stability, if necessary, pursuing a careful reconstruction/reinsertion of the ligamentousand myotendinous apparatus, an accurate implant cementation to prevent possible aseptic complications. Elbowreplacement is routinely used in its variants in patients often affected by various comorbidities and therefore moreexposed to mechanical or infectious complications. Even with results which are still not comparable to THR or TKR,elbow replacement can be considered an interesting systemcharacterised by rather fast recovery times and good resultsin terms of pain relief and functional improvement. The complexity of the surgical technique and the still limitednumbers of implants suggest to centralise this pathology in reference centres.